Quality of work life, Leadership, and Organizational Commitment influence Job performance among employees of the Bank for Agriculture and Agricultural Cooperatives (BAAC) under the Western Region Branch Affairs Division. - Sumlub, Walaipon; Lekkakul, Chanatip (Journal for Developing the Social and Community, 2025)
Background and Aims: This research examines how quality of work life, leadership, and organizational commitment influence job performance among employees of the Bank for Agriculture and Agricultural Cooperatives (BAAC) under the Western Region Branch Affairs Division. The objectives were to (1) investigate aspects of quality of work life that affect employees’ job performance, (2) explore leadership characteristics that affect employees’ job performance and (3) assess organizational engagement that affects employees’ job performance within this context. Methodology: Data was collected from a sample of 302 respondents using a questionnaire. The data were analyzed using descriptive statistics percentage, mean, and standard deviation and inferential statistics through statistical hypothesis testing. Results: The majority of respondents were female, aged 31–40 years, married, held a bachelor’s degree, had an average monthly income of 15,000–45,000 THB, and a tenure of 11–15 years. Overall, quality of work life was rated at a very high level, particularly with respect to the work environment and opportunities for development and career growth. Leadership was also rated at a very high level, especially regarding vision and flexibility. Organizational engagement was similar at a very high level, with the sense of belonging and dedication receiving the highest scores. Job performance was reported at a very high level overall, notably in work quality and timeliness of task performance. Conclusion: Hypothesis testing indicated that quality of work life, leadership, and organizational engagement were each positively associated with job performance at the 0.01 level of statistical significance. These findings provide actionable guidance for organizational policy and strategy to develop employees’ capabilities and strengthen organizational engagement, thereby enhancing overall job performance.